Weak Vertical Surface Movement Caused by the Ascent of the Emeishan Mantle Anomaly. Issue 2 (17th February 2018) - Zhu, Jiang; Zhang, Zhaochong; Reichow, Marc K.; Li, Hongbo; Cai, Wenchang; Pan, Ronghao
Abstract: Prevailing mantle plume models reveal that the roles of plume‐lithosphere interactions in shaping surface topography are complex and controversial, and also difficult to test. The exposed and complete strata in the Emeishan large igneous province (LIP) recorded abundant paleoenvironmental information associated with preeruptions and syneruptions, attracting numerous workers to this province to test these models. Despite intensified research these models are still strongly debated. This study represents an extensive field investigation combining new and previously published data from the Emeishan LIP to further seek information on plume‐induced topographic variations. Our results indicate that there are inconspicuous vertical motions of the surface topography during the ascent of mantle plume, and a significant surface subsidence occurred at the early stage of the volcanism that has a significantly positive correlation with the thickness of local lavas, and the topographic uplift emerged in the late stage of the volcanism. Our studies provide key geological and geochemical evidence that the ascent of the Emeishan plume is unable to drive a significant surface uplift, owing to the plume containing numerous entrained bodies of dense recycled oceanic crust (10–20%) that can significantly reduce plume buoyancy. The significant surface subsidence maybe linked to a significant loss of thermal buoyancy due to the release of heat, which, accompanied by rapid loading of numerous dense erupted lava and a strong lithospheric flexure, also lead to a later synchronous and significant surface subsidence in the Emeishan LIP. Key Points: Neither significant surface uplift nor subsidence emerged during the ascent of the Emeishan mantle anomaly Entrained recycled dense oceanic crust is responsible for a reduced buoyancy of the Emeishan plume Prolonged surface subsidence through strong lithospheric flexure is caused by basalt load in the Emeishan province